2003
DOI: 10.2527/2003.8192352x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of breed and intrauterine crowding on fetal erythropoiesis on day 35 of gestation in swine1

Abstract: In a previous report, it was suggested that intrauterine crowding impaired fetal erythropoiesis and that fetal erythropoiesis was accelerated in Meishan pigs during early pregnancy. Because these conclusions were based on limited numbers of observations, the present experiment was undertaken to provide a more extensive investigation of these phenomena. Intact white crossbred gilts, unilaterally hysterectomized-ovariectomized (UHO) white crossbred gilts, and intact Meishan gilts (n = 13 to 16 per group) were ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 13 publications
1
18
1
1
Order By: Relevance
“…Deficiencies in folate lead to abnormal erythropoiesis [3] and birth defects [4]. Previous results suggest that the amount of folate available to the developing conceptus influences fetal erythropoiesis [5] and fetal erythropoiesis influences uterine capacity of swine [5][6][7]. In addition, it has been reported that folate supplements increased the survival rate of fetuses 1 Supported by CSREES grant 2001-35203-11241.…”
Section: Introductionmentioning
confidence: 99%
“…Deficiencies in folate lead to abnormal erythropoiesis [3] and birth defects [4]. Previous results suggest that the amount of folate available to the developing conceptus influences fetal erythropoiesis [5] and fetal erythropoiesis influences uterine capacity of swine [5][6][7]. In addition, it has been reported that folate supplements increased the survival rate of fetuses 1 Supported by CSREES grant 2001-35203-11241.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Vallet et al (2003) suggested that fetal growth rate is less sensitive to intrauterine crowding than placental growth rate and that, as in the prolific Meishan female (Ford & Youngs 1993), an increase in placental efficiency may initially protect the developing fetus from a limitation in placental size. However, conclusions based only on a consideration of fetal weight may overlook critical effects on fetal development established early in gestation.…”
Section: Introductionmentioning
confidence: 99%
“…1998). Furthermore, fetal erythropoiesis in Meishan gilts was accelerated compared to White crossbred gilts, suggesting that faster development of mature blood cells could be beneficial to fetal survival in swine (Vallet et al . 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Reports have suggested that uterine capacity may be influenced by fetal erythropoiesis (Pearson et al . 1998; Vallet et al . 2002, 2003).…”
Section: Introductionmentioning
confidence: 99%